This Rebellious Terrain - Price, Daniel (2004)
The difficulty of situating humanity in relation to the promise of transcendence—in a time when God's absence dominates our thinking—arises from a refusal to simply affirm life's passage either into the divine or into a greater secular community. Various versions of the sacred that claim to surpass traditional metaphysics, including Bataille, Derrida, Heidegger and Schelling, are examined here in light of the general claims of movement and affirmation. In particular, the affirmation of deconstruction is connected to a metaphysics that posits a necessary movement of thought, and thus the effacement of death, while the address of poetry is situated in the refusal of that necessity. In other words, instead of speaking of the power of poetry (or the divine), we should speak of the fragility of its necessity.